ISLAM DAN LEMBAGA NEGARA - Rizka Julia Hermaniawati; Nur Sahraini Wanisa Wanisa; Resa Heryadi Yusup (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The creation of a state in a group of people has obvious urgency. The more people who occupy a territory, the more important the presence of the state in it. When a group of people gather in one area and relate to each other to fulfill their needs, it is not impossible that they will do something that causes chaos and harms others. Here, there must be someone who regulates the relationship between humans in order to create a fair and peaceful national life. Of course this role can be carried out by the state. The state can impose its power and regulate laws in order to create a just and peaceful life of the nation. The methodology used is library research. This research requires a lot of existing literature to complete the things needed for the completion of this research. The conclusion of this research is that the Qur'an has explained how state institutions should run in a Muslim country.